The degree of liver injury determines the role of p21 in liver regeneration and hepatocarcinogenesis in mice - Buitrago Molina, Laura Elisa; Marhenke, Silke; Longerich, Thomas; Sharma, Amar Deep; Boukouris, Aristeidis E.; Geffers, Robert; Guigas, Bruno; Manns, Michael P.; Vogel, Arndt (Hepatology, 2013)
Hepatocellular carcinoma (HCC) frequently arises in the context of chronic injury that promotes DNA damage and chromosomal aberrations. The cyclin-dependent kinase inhibitor p21 is an important transcriptional target of several tumor suppressors, which promotes cell cycle arrest in response to many stimuli. The aim of this study was to further delineate the role of p21 in the liver during moderate and severe injury and to specify its role in the initiation and progression of HCC. Deletion of p21 led to continuous hepatocyte proliferation in mice with severe injury allowing animal survival but also facilitated rapid tumor development, suggesting that control of compensatory proliferation by high levels of p21 is critical to the prevention of tumor development. Unexpectedly, however, liver regeneration and hepatocarcinogenesis was impaired in p21-deficient mice with moderate injury. Mechanistically, loss of p21 was compensated by activation of Sestrin2, which impaired mitogenic mammalian target of rapamycin (mTOR) signaling and activated cytoprotective Nrf2 signaling. Conclusion: The degree of liver injury and the strength of p21 activation determine its effects on liver regeneration and tumor development in the liver. Moreover, our data uncover a molecular link in the complex mTOR, Nrf2, and p53/p21-signaling network through activation of Sestrin2, which regulates hepatocyte proliferation and tumor development in mice with liver injury. (Hepatology 2013;53:1143-1152)
Gesehen am 02.12.2020